DESKRIPSI KESALAHAN KONSEP SISWA PADA MATERI KESETIMBANGAN KIMIA DI SMAN 1 TELUK KERAMAT - Adawiyah, Robiatul; ., Masriani; Putra, Rody (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aims to describe the causes and forms of student misconceptions on chemical equilibrium materials. Total 67 students from grade XI IPA 1 and XI IPA 2 were selected as research subjects. Student response data was collected through validated instrument in the form of essay test. The results of the data collection show that students experience concept errors in chemical equilibrium materials caused by lack of language mastery, material understanding, weak memory and learning resources. The forms of student misconceptions are the misinterpretation of the term (5.48%) with indicators misunderstanding chemical terms. Error of interpreting the concept (43.43%) with the wrong indicator dtermines the definition of chemical equilibrium, incorrectly determines the equilibrium formula or symbol of chemical equilibrium and understands the concept only partially. Error interpreting principle (16,42%) with wrong indicator to understand Le Chatelier and catalyst principle. Keywords: Concept Error, Chemical Equilibrium